APPLICATION OF THEORY PLANNED BEHAVIOR AND INFLUENCE ON CUSTOMER’S INTENTION ADOPTING ISLAMIC BANKING PRODUCT - Halid, Sitti N.; Worang, Frederik G.; Tumewu, Ferdinand (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: People nowadays have diverse plan in the future and each plan certainly needs cost planning. Most of them having trouble to manage their finances consistently. Therefore, Bank Muamalat offer it’s product (Tabungan iB Hijrah), to help customers to effective achieve their future goals based on Islamic law. This study aims to analyzing the customer’s intention to adopt Islamic Banking product in Bank Muamalat, Manado using the Theory Planned Behavior model (Attitude, Subjective Norms, Perceived Behavioral Control). This study uses quantitative method. Questionnaire is used to collect the data. This research derived and examined the model through multiple linear regression model in a sample of 90 respondents which are customer of Bank Muamalat, Manado. Finding of this research shows that Subjective Norm influences customer’s intention to adopt islamic banking product in Bank Muamalat, Manado significantly. While, Attitude and Perceived Behavioral Control do not have  influence on customer’s intention to adopt the product. From the result, it is recommended for the policy makers related to manager and marketers to provide adequate information in campaigning the product, promote the customers about the differences and benefits of Islamic Banking Product. Keywords: islamic banking, theory planned behavior, customer’s intention to adopt